Bienestar psicológico en adultos mayores que presentan enfermedad renal cronica G5 (2020)
The changes experienced by older adults are determined by the presence of diseases with a high degree of complication that affect health and emotional well-being. This research aimed to describe psychological well-being in older adults with G5 chronic kidney disease in the Quindío department. The work was developed from a quantitativedescriptive methodology, with a sample of 30 older adults with chronic kidney disease, who responded to the instrument of sociodemographic characteristics and psychological well-being of Ryff (1989) that contains 6 dimensions: autonomy, purpose of life, selfacceptance, mastery of the whole, personal growth and positive relationships. This investigation delved into the theoretical references of psychological well-being by Ryff (1989), Erikson (1985) and other authors. The results obtained showed that this sample has high levels of psychological well-being, with the dimension of positive relationships with others contributing the least to this variable.